Olly : race, class and gender in the invention of a rustic modernity - Reinheimer, Patrícia (Common Ground, 2020)
"This is a story about a weaver, Olly Reinheimer. Through the trajectory of her life and work, we can see that freedom and subalternization are not necessarily opposites. In the 1960s, her name became synonymous with art and fashion. She mixed various other techniques, such as sewing, painting, embroidery, and etching. She also worked in dimensions beyond clothing, such as the production of handmade paper. Her production in fabrics circulated mainly in Rio de Janeiro, São Paulo, Belo Horizonte and Curitiba (and some Latin American countries) and was presented in museums and galleries dedicated to exhibiting Modern Art. Until the end of the 1970s, the things produced by this artist were associated implicitly and explicitly with modernity, tropical nature, feminine sensuality, and being Brazilian. Although her work was briefly popular, she quickly slipped into oblivion after her death and therefore little is known about her today. Thus, this work presents her artistic trajectory and outlines her role in developing a decorative style particular to domestic spaces inhabited by a new intellectual middle class in the 1960s and 1970s in Brazil. Moreover, her story also avails itself to a feminist reading about the role of textile production and decorative arts in the process of institutionalizing design in Brazil"--